Is Gestational Diabetes Mellitus an Important Contributor to Metabolic Disorders in Trinidad and Tobago? - M. Clapperton; J. Jarvis; K. Mungrue (Obstetrics and Gynecology International)
Objective. To investigate the incidence of Gestational Diabetes Mellitus at the Mt. Hope Women's Hospital and to describe its epidemiological pattern. Design. A retrospective observational study (Jan 2005 to Dec 2007). Setting. A teaching hospital of The University of the West Indies. Population/Sample. Pregnant women who gave birth. Methods. A sample size of 720. The variables analyzed were: age, ethnicity, BMI of mother, family history of diabetes; history of GDM, obstetric history, birth weight and APGAR score of infant. Main Outcome Measures. (1) Incidence of cases of GDM. (2) Impact of the measured variable. Chi-squares, odds ratios and logistic regression were performed. Results. The incidence of GDM was 4.31% (95% C.I. 2.31%, 6.31%). The proportion of GDM patients for the years 2005, 2006, and 2007 were 1.67%, 4.58%, and 6.67%, respectively. Age, Obesity Ethnicity, Family history of diabetes and a history of GDM were determined risk factors. Associations between GDM and (1) Mode of Delivery and (2) APGAR score of the baby were found. Discussion & Conclusion. There was an apparent increase in the incidence of GDM. Additional studies should be conducted to measure the occurrence of GDM in Trinidad and Tobago. Efforts to promote public awareness and a healthy lifestyle should be made to reverse this trend.